Prevalence and predictive determinants of overweight and obesity in children aged 0-24 months in Morocco: a cross-sectional study - Fatima Zohra Benayad; Samia El Hilali; Rachid Razine; Karim Sbai Idrissi; Redouane Abouqal; Hajar Belhaj; Ahmed Kharbach; Majdouline Obtel (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. Preventing overweight and obesity in early childhood is a priority for healthcare systems worldwide due to the harmful effects on health and economy over the medium and long term. Objective. The aim of this study is therefore the identification of the determinants predictive of overweight and obesity during the first 24 months of a child's life. Material and Methods. From May 2021 to January 2022, 1012 mother-child pairs were included in this study and were interviewed at urban and rural health centers in the Skhirat-Temara in Morocco prefecture using a questionnaire. The anthropometric measurements of the children were also taken according to World Health Organization standards. Results. The prevalence of overweight and obesity in children aged 0-24 months was 16.5%. This prevalence increased with age (12.5% for the 0-6 months group, and 15.5% and 21.5% respectively for the 7-12 months and 13-24 months groups). Cesarean delivery (aOR=1.78; 95%CI: 1.26-2.51; p=0.001), more than two living siblings in the household (aOR=1.48; 95%CI: 1.03-2.12; p=0.03), male gender (aOR=1.56; 95%CI: 1.10-2.20; p=0.01), and child age (aOR=0.94; 95%: 0.92-0.97; p <0.001) are significant predictors of overweight and obesity. Paternal smoking (aOR=2.16; 95%CI: 1.15- 4.06; p=0.01), short sleep duration (aOR=4.05; 95%CI: 1.27-12.88; p=0.01) in children aged 7-12 months, and combined breastfeeding (aOR=5.88; 95%CI: 2.07-16.72; p<0.001) during the first six months in children aged 13-24 months are also predictive determinants for this problem. Conclusion. The identification of early predictors of overweight and obesity can be used by public health decision-makers as a roadmap for action to prevent and improve health.